2010
DOI: 10.1016/j.gaitpost.2010.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Decreased static and dynamic postural control in children with autism spectrum disorders

Abstract: The purpose of this study was to investigate postural control in children with Autism Spectrum Disorders (ASD) during static and dynamic postural challenges. We evaluated postural sway during quiet standing and the center of pressure (COP) shift mechanism during gait initiation for thirteen children with ASD and twelve age matched typically developing (TD) children. Children with ASD produced 438% greater normalized mediolateral sway (p<0.05) and 104% greater normalized anteroposterior sway (p<0.05) than TD ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(103 citation statements)
references
References 30 publications
5
91
1
6
Order By: Relevance
“…Moreover, pregnant women who reported falling demonstrated reduced movement of the COP when responding to translational perturbation while standing on a movable platform 40) . Further, children with autistic disorder who exhibit less agerelated development and postural instability also have decreased COP shift in the M-L direction while initiating gait, compared to age-matched normally developing children 41) . Therefore, it is plausible that the significantly increased displacement of the COP seen in the present investigation is indicative of increased dynamic postural stability in the participants with PD who practiced the TC exercise.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, pregnant women who reported falling demonstrated reduced movement of the COP when responding to translational perturbation while standing on a movable platform 40) . Further, children with autistic disorder who exhibit less agerelated development and postural instability also have decreased COP shift in the M-L direction while initiating gait, compared to age-matched normally developing children 41) . Therefore, it is plausible that the significantly increased displacement of the COP seen in the present investigation is indicative of increased dynamic postural stability in the participants with PD who practiced the TC exercise.…”
Section: Discussionmentioning
confidence: 97%
“…Poorly developed balance skills in children -regardless of pathology -may reduce the capability to develop more complicated movement skills, which, in turn, may hamper social development and the willingness to participate in sports [13]. Furthermore, a number of studies have analyzed postural sway, and have found postural abnormalities in ASD in various postural tasks, such as quiet standing and looking straight ahead [14][15][16], quiet standing and dual-tasking [17], quiet standing with the eyes closed [8], quiet standing on a sway-referenced platform [18], and quiet standing while performing visual search [19]. Also, postural instability appeared related to symptom severity regarding the occurrence of repetitive behaviors [8].…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in the M-L displacement of COP while initiating gait was reported in older adults with disabilities, as compared to healthy older adults 40,41) . Furthermore, children who show less age-related development and postural instability also have reduced M-L COP movement when initiating gait, compared to age-matched normally developing children 56) .…”
Section: Discussionmentioning
confidence: 99%